Taking liberties : the war on terror and the erosion of American democracy - Herman, Susan N. (Oxford Univ. Press, 2011)
"Since 9/11, the U.S. government has acted in a variety of ways--some obvious, some nearly invisible--to increase its surveillance and detention power over American citizens and residents. While most of us have made our peace with the various new restrictions on our civil liberties after 9/11, we have done it without really understanding what those restrictions are or the extent of their reach. Moreover, we tend to think that if the national security state overreaches, we shouldn't worry--the courts will come to the rescue and rein it in. In Taking Liberties, Susan Herman explains how this came to be. Beginning in late 2001, the Bush Administration undertook a series of measures, some of which were understandable and valid given the context, to expand federal surveillance authority. Yet as she shows through a series of gripping episodes involving ordinary Americans, they overreached to the point eroding basic constitutional liberties. Herman spells out in vivid detail why all Americans should be worried about the governmental dragnet that has slowly and at times imperceptibly expanded its coverage over the American public. The erosion of civil liberties doesn't just impact immigrants, Americans of Middle Eastern descent, or Guantanamo detainees, but any American who appears to be engaging in provocative political activity. Taking Liberties is a wake-up call for all Americans, who remain largely unaware of the post-9/11 surveillance regime's insidious and continuing growth"--